New Geothermal Prospect in North-Eastern Morocco - Rimi, Abdelkrim (2010)
Geothermal data has been indicating promising potentialities in the north-eastern Morocco. This paperpresents new temperature data, recently recorded in water borehole located in the Berkane and Oujda areas. Generally, the observed temperature gradients are rather high. One hole near Berkane, revealed an average geothermal gradient of more than 110 ºC/km at depths greater than 300 m. This result confirms the geothermal gradient estimated in a mining borehole located about 30 km west of the Berkane borehole, in which water temperatures of 96 ºC are reached at a depth of about 700 m. Such a high geothermal gradient, exceeding by far the ones already determined for northeastern Morocco, could act as a stimulus to programs aimed at the geothermal exploitation of high temperature aquifers.